Development of a System for Improving Future Teachers’ Readiness for the Child’s Spiritual and Moral Development in a Cross-Cultural Space - Shevchenko, Ylia; Moskalyova, Luydmyla; Kanarova, Olga; Poznanska, Olga (Journal of History Culture and Art Research, 2019)
Nowadays higher education is developing in accordance with new needs of modern school. The main task of this process is to provide necessary conditions for the spiritual and moral development of the child’s personality. This task determines the emergence of new approaches and innovative pedagogical tools, which include information and communication technologies. In this regard, the issue of future teacher’s competence in the field of new and creative performance of educational tasks is being actualized. The article describes a specially designed system, which is aimed at the improvement of future teacher’s readiness for the child’s spiritual and moral development by means of using traditional Ukrainian fairy tales – SMDC (spiritual and spiritual development of the child). SMDC requires the use of information and communication technologies. This is a pedagogical tool, which is designed for students of the Bachelor’s degree program in Primary Education. The system requires: 1) development of a package of multimedia materials; 2) selection of educational materials, which contain tools for the child’s spiritual and moral education; 3) creation of students’ own materials, which are aimed at their personal and professional development.